Disproportions in proportional distributions - Misztal, Andrzej (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
In the case of degressive proportionality, a large over-representation of small countries is a deliberate concession of larger countries to ensure that less populated states are adequately represented (the principle of European solidarity). It is worth emphasizing how important is the role played by election thresholds, which prevent excessive fragmentation of the parliament. Thus, they act as a stabilizing factor in the political scene, which in Polish conditions cannot be overestimated. A weakness of the thresholds is the fact that they distort the proportionality of the results and cause over-representation of certain parties. In extreme cases they can lead to the dictatorship of one party even if it is provided with low popularl support.
Mathematical Economics, 2013, Nr 9 (16), s. 89-104
Keywords: electoral threshold; degressive proportionality; over-representation; proportionality